Save a trip: Clinical outcomes of cardiac allografts recovered by local surgeons compared to recipient center surgeons. - Awab Ahmad, MD; Timothy R. Harris, MD; Aaron Williams, MD; Alexandra DeBose-Scarlett, MD; Rubayet Kamal, BS; Enock Atta Adjei, MD; Hasan K. Siddiqi, MD; Chen Chia Wang; Mark Petrovic; Clifton D. Keck; Shelley R. Scholl, RN; Ashish S. Shah, MD; et al. (JHLT Open)
Background: Local surgeon recovery of donor livers and kidneys is common and well-studied. This practice is rare and poorly studied in cardiac transplantation. We examined clinical outcomes of cardiac allografts recovered by local surgeons vs. recipient institution surgeons. Methods: A retrospective review of all recoveries of adult cardiac allografts from brain dead donors for a single academic transplant center between 1/2020 and 12/2021 was performed. Donor and recipient baseline characteristics, distance traveled and ischemic time, and recipient outcomes were collected. Primary graft dysfunction (PGD) was determined based on 2014 ISHLT guidelines. Results: 218 recovery attempts were included, 25 conducted by local surgeons. Donor demographics between the two groups were similar, with a mean age of 31.5±10 years. There was a non-significant trend towards higher acceptance rates by local surgeons compared to recipient center surgeons (96% vs 82.9%, p=0.139). Ischemic times (208±28 vs 176±61 min p=0.003) and travel distances (788 vs 615 miles, p=0.011) were longer in the local recovery group. There was no difference in severe PGD (4.2% vs 7.5%, p=1.0), moderate/severe PGD (12.5% vs 14.4%, p=0.22) or 30-day survival (95.8% vs 95%, p=0.218) between the local surgeon and recipient center recovered allografts. Conclusion: Cardiac allografts recovered by a local surgeon team are high quality with similar rates of organ acceptance, PGD, and 30-day survival. This provides evidence that leveraging the expertise of the local surgical team is a safe and effective method for decreasing travel risks, financial expenditure, and opportunity cost associated with cardiac allograft recovery.